The Position of the Accountant Profession in the Anathema Hadith for Usury Transaction Actors - Ahmad Arief; Abd. Rahman Sakka; La Ode Ismail Ahmad; Rusmin Abdul Rauf (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
This article aims to analyze the position of the Accountant profession and the hadith of anathema for usury transaction actors. Accountants as prefetions will be indispensable in trasaksi, there is even an order there is a profession that records transactions in the Quran. However, it will be a problem when the transaction is a usury transaction. In the hadith, the Messenger of Allah circumcised the author of usury transactions. In this case it is an accountant. This article is a hadith study that uses a maudūī (thematic) approach. The article finds that there are scholarly disagreements with the profession. There are those who absolutely forbid and there are those who allow on condition that they are allowed on the condition that they try to eliminate the awarid al-muktasabah (a barrier that can be attempted to be removed) namely the inability to detect usury by studying all related elements in usury transactions.